In vitro gill cell monolayer successfully reproduces in vivo Atlantic salmon host responses to Neoparamoeba perurans infection. Issue 86 (March 2019) - Cano, Irene; Taylor, Nick GH.; Bayley, Amanda; Gunning, Susie; McCullough, Robin; Bateman, Kelly; Nowak, Barbara F.; Paley, Richard K.
Abstract: An in vitro model to study the host response to Neoparamoeba perurans, the causative agent of amoebic gill disease (AGD), was evaluated. The rainbow trout gill derived cell line, RTgill-W1, was seeded onto permeable cell culture supports and maintained asymmetrically with apical seawater. Cells were inoculated with either a passage attenuated or a recent wild clone of N. perurans . Amoebae, loaded with phagocytosed fluorescent beads, were observed associated with host cells within 20 min post inoculation (pi). By 6 h small foci of cytopathic effect appeared and at 72 h cytolysis was observed, with total disruption of the cell monolayer at 96 h pi. Due to cell monolayer disruption, the platform could not support proliferation of amoebae, which showed a 3-log reduction in parasite 18S rRNA mRNA after 72 h (10 6 copies at 1 h to 10 3 at 72 h pi). SEM observations showed amoebae-like cells with either short pseudopodia and a malleiform shape, or, long pseudopodia embedded within the gill cells and erosion of the cell monolayer. To study the host immune response, inoculated gill cells were harvested from triplicate inserts at 0, 1, 3, 6, 24 and 48 h pi, and expression of 12 genes involved in the Atlantic salmon response to AGD was compared between infected and uninfected cells and between amoebic clones. Both clones induced similar host inmate immune responses, with the up-regulation of proinflammatory cytokine IL1β, complement C3 and cell receptor MHC-1. The Th2 pathway was up-regulated, with increased gene expression of the transcription factor GATA3, and Th2 cytokines IL10, IL6 and IL4/13A. PCNA and AG-2 were also up-regulated. The wild clone induced significantly higher up-regulation of IL1β, MHC-1, PCNA, lysozyme and IL10 than the attenuated clone for at least some exposure times, but AG-2 gene expression was higher in cells inoculated with the attenuated one. A principal component analysis showed that AG-2 and IL10 were key genes in the in vitro host response to N. perurans . This in vitro model has proved to be a promising tool to study host responses to amoebae and may therefore reduce the requirement for in vivo studies when evaluating alternative therapeutants to AGD control. Highlights: In vitro gill epithelia model enabled study of host response to Neoparamoeba perurans . The association of the parasite to the monolayer was studied by SEM. A protocol for live cell imaging of N. perurans is described. Host cytokines related to Th2 and cell proliferative pathways were up-regulated.